Macro Variable Influence and Company Fundamental Factors against Changes in Go Public Banking Stock Prices on the In-donesia Stock Exchange for the Period 2004-2007 (Case Study on Bank Danamon, Bank BRI, Bank BCA, Bank UOB Indonesia, Bank Niaga and Bank S - Ary Novianto, Robertus; Sugianto Yusuf, Paulus (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the effect of macroeconomic factors and company fundamental factors on changes in banking stock prices using explanatory. The unit of analysis of this study is a bank that is listed on the Indonesian Stock Exchange. Populations of this study are stock price, ROA, and LDR for 5 years that divide to semester and inflation and gross domestic product. This study is stock price, ROA, and LDR for 6 banking for 5 years. The results of this study indicate that there are significant simultaneous effects between macroeconomic factors and company fundamental factors towards changes in banking stock prices. Partially macroeconomic factors have a positive influence on banking stock prices, as well as company fundamental factors, which have a partially positive influence on banking stock prices.